Long-term survival without surgical intervention in a patient with a natural history of a single right ventricle: A case report. Issue 2 (August 2021) - Kubota, Kana; Imai, Yasushi; Ishiyama, Yusuke; Kataoka, Koichi; Ohki, Gaku; Kawada, Masaaki; Kario, Kazuomi
Abstract: Single ventricle (SV), a complex cardiac anomaly, if left untreated, is thought to lead to a poor prognosis. Herein, we report the case of a long-term survivor with an unrepaired SV with right ventricle (RV) morphology. A 55-year-old man presented with a SV with RV morphology, with a double outlet, large atrial septal defect, common atrioventricular valve, pulmonary valve stenosis (PS), and dextrocardia. Because the native PS provided adequate restriction of the pulmonary blood flow, he did not develop pulmonary hypertension; however, he had severe cyanosis. In patients with SV and moderate PS, even if the SV has RV morphology, long-term survival may be possible without surgical intervention. <Learning objective: Single ventricle (SV) is a rare and complex congenital heart disease. Outcomes of patients with SV are generally poor; however, some patients can survive long-term without surgical intervention. In particular, it may be possible for patients with SV and moderate pulmonary artery stenosis to enjoy long-term survival without surgical intervention, even if the SV has right ventricular morphology.>